PEMODELAN GROUP DECISION SUPPORT SYSTEM (GDSS) SELEKSI PENERIMAAN ASISTEN DOSEN PADA PERGURUAN TINGGI XYZ DENGAN MADM TOPSIS DAN VOTING MODEL BORDA: BORDA, GROUP DECISION SUPPORT SYSTEMS, MULTI ATTRIBUTE DECISION MAKING, TOPSIS - Puspitorini, Sukma; Rosmalia, Lia; Nanny (FORTECH (Journal of Information Technology), 2018)
Group decision support system (GDSS) of assistant lecturer is a decision support systemsmodeledto help a group of decision maker assessing students that enroll as lecturer assistant applicant. The decision model used in this research is Multi Attribute Decision Making (MADM) TOPSIS method with 10  assessment criteria that is grades (C1), cumulative index (C2), Teaching Skill (C3), Mastery of Material (C4), Class Mastery (C5), Cooperation (C6), Motivation (C7), Discipline (C8), Responsibility (C9), and Experience (C10) while the group decision using the Borda voting model.The result of this research is the decision making model of the assessment of prospective lecturer assistant in group.